Delivery of siRNA Using Functionalized Gold Nanorods Enhances Anti-Osteosarcoma Efficacy - Zhang, Man; Lin, Jinti; Jin, Jiakang; Yu, Wei; Qi, Yiying; Tao, Huimin (Frontiers in Pharmacology, 2021)
Gold nanorods (GNRs) are intensively explored for the application in cancer therapy, which has motivated the development of photothermal therapy (PTT) multifunctional nanoplatforms based on GNRs to cure osteosarcoma (OS). However, the major limitations include the toxicity of surface protectant of GNRs, the unsatisfactory in targeting therapy and the resistant effects of photothermal-induced autophagy, thus increasing the risk of relapse and metastasis of OS. In this present paper, we designed and synthesized the GNRs multifunctional nanoplatforms using a layer-by-layer assembly, so as to deliver transcription factor EB (TFEB)-siRNA targeting autophagy and tumour-targeting cell penetrating membrane peptide (CPP), and the synthesized GNRs@siRNA/CPP nanoplatforms exhibits excellent biocompatibility, robust near-infrared (NIR) photothermal conversion and precise deliverable ability of siRNA. In addition, PH-sensitive CPP could improve the tumour-targeting ability of the GNRs nanoplatforms. Moreover, the gene (targeting lysosomal formation) and photothermal exhibit excellent synergistic anti-OS efficacy. Meanwhile, it is worth noting that the GNRs nanoplatforms groups have anti-lung metastasis of OS. This study provides a new reference for the improvement of the efficacy of OS clinically.